血液透析血管通路专科护士核心能力 评价指标体系的构建. - ZHANG Yingjun; CHEN Lin; LIU Li; LI Qiao (Chinese Nursing Research, 2021)
Objective: To construct the Core Competency Evaluation Index System for Hemodialysis Vascular Access Specialized Nurses. Methods: According to the content of foreign literature on the role of hemodialysis vascular access nurses, the Core Competence Evaluation Index System for Hemodialysis Vascular Access Specialized Nurses was formed through expert interview, subject group discussion and Delphi method. Results: Two rounds of expert consultations were conducted. The positive coefficients of experts in the two rounds of consultations were both 100%. The authority coefficient of experts was 0. 895. The developed Core Competency Evaluation Index System for Hemodialysis Vascular Access Specialized Nurses included 6 first-level indicators, 16 second-level indicators and 43 third-level indicators. Conclusion: The established Core Competency Evaluation Index System for Hemodialysis Vascular Access Specialized Nurses was scientific and reliable, which could provide reference for further developing the training program and curriculum of hemodialysis vascular access nurse specialists in the future.